x^2 = y ... y is a variable, not a constant like 4 ... different rules apply a^y = b^x a = b^(x/y) until you know a number value for b and y (which has become a root) we don 't know if the answer is pos, neg, or imaginary.

2 Answers · Education & Reference · 30/03/2020

... + Fr = mh''. Use the correct signs for the

**LHS**terms. Fg is a constant [which one?]. Note that h'...1 Answers · Science & Mathematics · 28/02/2020

**LHS**= xy + xy' = x(y + y') ..........distributive law = x(1) = x RHS = (x+y)(x+y' ) = x+(yy') ...........distributive law = x+(0) .............complement law = x**LHS**= RHS1 Answers · Science & Mathematics · 03/08/2019

...x = c/d Then x = (c/d) - (a/b) RHS is clearly rational while

**LHS**is irrational. This is a contradiction. Hence the sum must...4 Answers · Science & Mathematics · 03/08/2019

... / R GmM / R = 2*KE and you should recognize the

**LHS**as being equal to -GPE. If you find this helpful, please award...1 Answers · Science & Mathematics · 07/05/2019

... the given P(t) and showing that it equals the

**LHS**. Or you can find the solution by solving the DE this way: ...1 Answers · Science & Mathematics · 14/02/2019

....N. (oxidation number) of H on the

**LHS**= O.N. of H on the RHS = +1...⁻ O.N. of H on the**LHS**= O.N. of H on the RHS, as...3 Answers · Science & Mathematics · 16/02/2019

...75707>pi-x>2.52611 {the principal values} Check: take x=0.609

**LHS**=ln[4-2(0.32723837...)]=1.20762311.. RHS=ln[3+0.32723837...]=1.20214264.. =>**LHS**...3 Answers · Science & Mathematics · 11/02/2019

It is the distributive law, but you have to *prove* that by showing the

**LHS**is a subset of the RHS and the RHS is a subset of the**LHS**and therefore**LHS**= RHS. Check the link below.1 Answers · Science & Mathematics · 06/02/2019

... by 5^2 each side to get 5^(b-1)*5^2 = 2 * 5^2. Simplify

**LHS**to get 5^(b-1 + 2) = 2 * 5^2 5^(b+1) = 2 * 5^2 U can compute the ...3 Answers · Science & Mathematics · 11/12/2018